Transversus abdominis plane block versus intraperitoneal local anesthetics in bariatric surgery: A systematic review and network meta-analysis - Chaw, Sook Hui (Springer Verlag, 2021)
Background: Transversus abdominis plane (TAP) block and intraperitoneal local anesthetics (IPLA) are widely investigated techniques that potentially improve analgesia after bariatric surgery. The analgesic efficacy of TAP block has been shown in previous studies, but the performance of TAP block can be difficult in patients with obesity. We performed a systematic review and meta-analysis to compare the analgesic efficacy of TAP block and IPLA. An alternative technique is useful in clinical setting when TAP block is not feasible. Methods: We searched PubMed, Embase, and CENTRAL from inception until August 2020 for randomized controlled trials comparing both techniques. The primary outcome was cumulative morphine consumption at 24 h. Secondary pain-related outcomes included pain score at rest and on movement at 2, 6, 12, and 24 h; postoperative nausea and vomiting; and length of hospital stay. Results: We included 23 studies with a total of 2,178 patients. TAP block is superior to control in reducing opioid consumption at 24 h, improving pain scores at all the time points and postoperative nausea and vomiting. The cumulative opioid consumption at 24 h for IPLA is less than control, while the indirect comparison between IPLA with PSI and control showed a significant reduction in pain scores at rest, at 2 h, and on movement at 12 h, and 24 h postoperatively. Conclusions: Transversus abdominis plane block is effective for reducing pain intensity and has superior opioid-sparing effect compared to control. Current evidence is insufficient to show an equivalent analgesic benefit of IPLA to TAP block.